The concept of character education in the digital era: A comparative study of imam az-zarnuji and jean piaget - Agung Ilham Prastowo; Amira Muflicha Daraini (At Turots: Jurnal Pendidikan Islam, 2024)
Digital era marked by an overflow of information, instant culture, and moral decline character education that relies solely on normative and authoritarian approaches is increasingly inadequate. This study aims to compare and synthesize the educational thoughts of Imam Az-Zarnuji and Jean Piaget to develop a more integrative approach to character education. This study utilizes a qualitative research method with a literature review approach. The data sources comprise scholarly works relevant to the character education perspectives of Imam Az-Zarnuji and Jean Piaget. Results of this research are Az-Zarnuji stressing the importance of spirituality, ethical conduct (adab), and sincerity in seeking knowledge, while Piaget focuses on moral autonomy, social responsibility, and the development of ethical reasoning. The synthesis of their perspectives offers a more holistic framework for character education suited to contemporary challenges. The study recommends that future research build a contextualized character education framework and examine its practical implementation in educational institutions to assess its effectiveness in fostering students' moral development